Clinical Features and Outcomes of Patients With Symptomatic Kaposi Sarcoma Herpesvirus (KSHV)-associated Inflammation: Prospective Characterization of KSHV Inflammatory Cytokine Syndrome (KICS) - Polizzotto, Mark N.; Uldrick, Thomas S.; Wyvill, Kathleen M.; Aleman, Karen; Marshall, Vickie; Wang, Victoria; Whitby, Denise; Pittaluga, Stefania; Jaffe, Elaine S.; Millo, Corina; Tosato, Giovanna; Little, Richard F.; et al. (Clinical infectious diseases, 2016)
Background. Kaposi sarcoma herpesvirus (KSHV) is the cause of Kaposi sarcoma (KS), primary effusion lymphoma (PEL), and a form of Castleman disease (KSHV-MCD). Recently a KSHV-associated inflammatory cytokine syndrome (KICS) distinct from KSHV-MCD was reported. Methods. We prospectively characterized the clinical, laboratory, virologic and immunologic features of KICS by evaluating symptomatic adults with KSHV using a prespecified definition. These features and overall survival were compared with controls from 2 prospectively characterized human immunodeficiency virus (HIV)-infected cohorts, including 1 with KSHV coinfection. Results. All 10 KICS subjects were HIV infected males; 5 had HIV viral load (VL) suppressed <50 copies mL (median 72, range <50–74 375); all had KS and 2 also had PEL. All had multiple severe symptoms attributable to KICS: median number of symptoms 8 (6–11), median grade of worst symptom 3 (2–4). These included gastrointestinal disturbance (present in 9); edema (9); respiratory (6); and effusions (5). Laboratory abnormalities included anemia (all); hypoalbuminemia (all) and thrombocytopenia (6). None developed KSHV-MCD; 6 died with median survival from KICS diagnosis 13.6 months. KICS subjects compared with controls had more severe symptoms; lower hemoglobin and albumin; higher C-reactive protein; higher KSHV VL; elevated interleukin (IL)-6 and IL-10; and an increased risk of death (all P < .05). Anemia and hypoalbuminemia at presentation were independently associated with early death. Conclusions. KICS subjects demonstrated diverse severe symptoms, a high rate of KSHV-associated tumors, high mortality, and a distinct IL-6/IL-10 signature. KICS may be an important unrecognized cause of morbidity and mortality, including symptoms previously ascribed to HIV. Exploration of KSHV-directed therapy is warranted.